Paper imbibition for timing of multi-step liquid handling protocols on event-triggered centrifugal microfluidic lab-on-a-disc platforms. Issue 3 (5th December 2014) - Kinahan, David J.; Kearney, Sinéad M.; Faneuil, Olivier P.; Glynn, Macdara T.; Dimov, Nikolay; Ducrée, Jens
Abstract : Imbibition of liquid along a paper strip offers enhanced flow control of dissolvable film valve on the centrifugal platform. Abstract : Rotational microfluidic platforms have attracted swiftly growing interest over the last decade due to their suitability for integration and automation of sample preparation and detection. Valving is of pivotal importance on these compact "Lab-on-a-Disc" (LoaD) platforms as all liquids are exposed to the same centrifugal field. A number of valving technologies have been developed to coordinate timing of serial and/or parallel multi-step/multi-liquid assay protocols comprising of laboratory unit operations (LUOs) such as the release, metering and mixing of sample and reagents. So far these valving techniques could be broadly categorised into rotationally controlled or externally actuated schemes. Only recently a new, "event-triggered" flow control has been introduced. In this approach, a valve is opened upon arrival of a liquid at a defined destination on the disc; this innovative mechanism for the first time permits the cascading of LUOs independent of the spin rate. In one technology, dissolvable films (DFs) are configured with a pneumatic chamber to offer function akin to an electrical relay. Dissolving one DF, termed the control film (CF), results in the release of liquid at a distal location through a so-called load film (LF). In this paper, a new method for temporal control of actuating DF-based, event-triggered CFs which are serially aligned at defined distances along a paper strip is introduced. Liquids are transported through the paper strip at a given velocity, thus setting well-defined intervals between subsequent LUOs, e.g. incubation steps. As a proof-of-concept, we present a disc with integrated metering and mixing which can perform a prototypical, 4-fold serial dilution; a common function in bioanalytical protocols. Imbibition of the paper strip sequentially opens five valves for serial dilution and mixing. To illustrate an unprecedented level of on-disc automation, this is followed by a branched cascade of 17 event-triggered valves (for a total of 22 liquid handling steps) which completes the serial dilution protocol.